Psychedelics, Sociality, and Human Evolution - Rodríguez Arce, José Manuel; Winkelman, Michael James (Frontiers in Psychology, 2021)
Our hominin ancestors inevitably encountered and likely ingested psychedelic mushrooms throughout their evolutionary history. This assertion is supported by current understanding of: early hominins’ paleodiet and paleoecology; primate phylogeny of mycophagical and self-medicative behaviors; and the biogeography of psilocybin-containing fungi. These lines of evidence indicate mushrooms (including bioactive species) have been a relevant resource since the Pliocene, when hominins intensified exploitation of forest floor foods. Psilocybin and similar psychedelics that primarily target the serotonin 2A receptor subtype stimulate an active coping strategy response that may provide an enhanced capacity for adaptive changes through a flexible and associative mode of cognition. Such psychedelics also alter emotional processing, self-regulation, and social behavior, often having enduring effects on individual and group well-being and sociality. A homeostatic and drug instrumentalization perspective suggests that incidental inclusion of psychedelics in the diet of hominins, and their eventual addition to rituals and institutions of early humans could have conferred selective advantages. Hominin evolution occurred in an ever-changing, and at times quickly changing, environmental landscape and entailed advancement into a socio-cognitive niche, i.e., the development of a socially interdependent lifeway based on reasoning, cooperative communication, and social learning. In this context, psychedelics’ effects in enhancing sociality, imagination, eloquence, and suggestibility may have increased adaptability and fitness. We present interdisciplinary evidence for a model of psychedelic instrumentalization focused on four interrelated instrumentalization goals: management of psychological distress and treatment of health problems; enhanced social interaction and interpersonal relations; facilitation of collective ritual and religious activities; and enhanced group decision-making. The socio-cognitive niche was simultaneously a selection pressure and an adaptive response, and was partially constructed by hominins through their activities and their choices. Therefore, the evolutionary scenario put forward suggests that integration of psilocybin into ancient diet, communal practice, and proto-religious activity may have enhanced hominin response to the socio-cognitive niche, while also aiding in its creation. In particular, the interpersonal and prosocial effects of psilocybin may have mediated the expansion of social bonding mechanisms such as laughter, music, storytelling, and religion, imposing a systematic bias on the selective environment that favored selection for prosociality in our lineage.